Temporal Variability of Rainfall and Trend Analysis of Melloulou Watershed in Morocco - Bertal Yassine; Ben Brahim Youssef (European Scientific Journal, ESJ, 2024)
This paper focuses on analyzing the temporal variability of rainfall and rainfall trends using a statistical analysis of rainfall data in the Melloulou watershed for a half-century chronicle (1970-2020). The objective of this study is to extract all the rainfall characteristics and the rainfall variability during this period to determine the rainfall trends. The working method is based on a statistical approach to detect the climatic characteristics of the Melloulou basin. The study of the standardized precipitation index (SPI) and the rainfall deficit index (RDI) showed the alternation of very long dry periods with wet periods. The Mann-Kendall test under the RStudio also showed a decreasing rainfall trend.